The Relationship of Training in Improving the Environment (Environment Centers at the University of Mosul as A Model) - Qasim, Rakan Farooq (Research in Business and Management, 2023)
The research aims to demonstrate the impact of training in improving the environment. The research sample was represented by trained persons in research and advisory centers, continuing education courses and training courses held annually by the University of Mosul, specifically the College of Engineering, for people affiliated with institutions, companies, offices and laboratories of the public and private sector in Mosul, and measuring the extent of their utilization. And its application in the labor market, and its repercussions on the environmental reality in the city. The researcher relied on the descriptive analytical method by relying on a questionnaire and analyzing it using the statistical analysis program (SPSS). The results showed that there is a positive and strong relationship between training programs and improving the environment, the more realistic the training programs meet the needs of the community, are clear and at the heart of the work and can be applied in practice, in addition to the maximum benefit from the programs as a result of the trainers' commitment to the curriculum and the time of the course, the more this contributes to improving the environment through investment. sound environment, developing environmental, economic and social awareness, as well as recognizing the role of institutions in achieving sustainable development, and vice versa. Study recommended Paying attention to training programs because of their impact on society, as the study showed a strong relationship between training programs and improving the environment, in addition to holding on-site training courses in the dysfunctional state institutions and companies.